2017
DOI: 10.1097/md.0000000000008179
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nonalcoholic fatty liver disease in patients with type 2 diabetes mellitus

Abstract: Background:Nonalcoholic fatty liver disease (NAFLD) is emerging as a public health issue worldwide and is highly prevalent in patients with type 2 diabetes mellitus (T2DM). However, there was a great disparity across studies in the estimated prevalence of NAFLD in T2DM patients. This meta-analysis, therefore, aimed to estimate the pooled prevalence of NAFLD in T2DM patients.Methods:Electronic databases of PubMed, Web of Science, Embase, Chinese National Knowledge Infrastructure, and Wanfang were searched using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
173
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(185 citation statements)
references
References 48 publications
9
173
1
2
Order By: Relevance
“…These data suggest that the prevalence of NAFLD in the general population is 20% to 40% with minor variation by age, region, or ethnicity, and that the incidence of disease is increasing over time in many countries (Table ). A recent meta‐analysis involving 35,599 patients with type 2 diabetes (T2D) reported that the pooled prevalence of NAFLD in these patients was 59.7% . Thus, NAFLD is very common in patients with T2D, with an estimated prevalence of 60% to 80%…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that the prevalence of NAFLD in the general population is 20% to 40% with minor variation by age, region, or ethnicity, and that the incidence of disease is increasing over time in many countries (Table ). A recent meta‐analysis involving 35,599 patients with type 2 diabetes (T2D) reported that the pooled prevalence of NAFLD in these patients was 59.7% . Thus, NAFLD is very common in patients with T2D, with an estimated prevalence of 60% to 80%…”
Section: Introductionmentioning
confidence: 99%
“…Older age (odds ratio (OR) = 1.099, p = 0.001), high body mass index (BMI) (OR = 1.088, p = 0.003), low platelet level (OR = 0.996, p = 0.014), and smoking (OR = 1.653, p = 0.013) are independent risk factors of advanced fibrosis (FibroScan > 10.6 kPa) among T2D patients [21]. The existence of T2D is closely associated not only with advanced fibrosis in cross-sectional data [22][23][24] but also with the rapid progression of hepatic fibrosis based on longitudinal data [14,18,[25][26][27][28]. Conversely, NAFLD patients have a higher risk of incidental T2D compared to non-NAFLD patients [27,28].…”
Section: Association Of T2d With Nash and Nafldmentioning
confidence: 98%
“…Among 10 studies that estimated the prevalence of NASH, the global prevalence of NASH among individuals with T2D is 37.3% (95% CI 24.7-50.0%). Seven studies estimated the prevalence of advanced fibrosis in T2D patients with biopsy-proven NAFLD to be 17% (95% CI 7.2-34.8%) [18]. Among 18.2 million people in the US living with T2D and NAFLD, 6.4 million have NASH [19].…”
Section: Association Of T2d With Nash and Nafldmentioning
confidence: 99%
“…It is estimated that approximately 7-30% will progress to NASH, which gives an estimated prevalence of NASH between 1Á5% and 6% (Younossi et al, 2016). As much as 60% of patients with type 2 diabetes suffer from NAFLD (Dai et al, 2017). The NASH diagnosis requires a liver biopsy confirming the presence of more than 5% steatosis, hepatocyte ballooning and lobular inflammation (European Association for the Study of the Liver (EASL) et al, 2016).…”
Section: Introductionmentioning
confidence: 99%